2023
DOI: 10.1099/ijsem.0.005706
|View full text |Cite
|
Sign up to set email alerts
|

Tamlana laminarinivorans sp. nov. and Tamlana sargassicola sp. nov., two novel species isolated from Sargassum, show genomic and physiological adaptations for a Sargassum-associated lifestyle

Abstract: The genus Tamlana from the Bacteroidota currently includes six validated species. Two strains designated PT2-4T and 62-3T were isolated from Sargassum abundant at the Pingtan island coast in the Fujian Province of China. 16S rRNA gene sequence analysis showed that the closest described relative of strains PT2-4T and 62-3T is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…T. laminarinivorans, T. sargassicola, and T. sedimentorum all contain two similar PULs related to alginate utilization. These PULs contain a similar set of CAZymes as ALG PUL, consisting of PL6, 7, and 17 (Li et al, 2023). However, their gene cluster structure and arrangement differ significantly from ALG PUL, which is consistent with the lineage and phylogenetic tree results (Figure 1).…”
Section: Alginolytic Pul In Strain S12supporting
confidence: 84%
See 3 more Smart Citations
“…T. laminarinivorans, T. sargassicola, and T. sedimentorum all contain two similar PULs related to alginate utilization. These PULs contain a similar set of CAZymes as ALG PUL, consisting of PL6, 7, and 17 (Li et al, 2023). However, their gene cluster structure and arrangement differ significantly from ALG PUL, which is consistent with the lineage and phylogenetic tree results (Figure 1).…”
Section: Alginolytic Pul In Strain S12supporting
confidence: 84%
“…Currently, there are nine species that have been validly published under the genus Tamlana. Tamlana species have been isolated from various sources, including seawater (Yoon et al, 2008;Liu et al, 2015;Jung et al, 2019), algae (Li et al, 2020;Li et al, 2023), marine sediment (Lee, 2007;Romanenko et al, 2014), and the gut of abalone (Cao et al, 2021). Research conducted by Li et al (2023) has shown that members of Tamlana possess a wide range of CAZymes that are associated with the utilization of algal polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations